Academic library buildings in the electronic age a study of planning and design considerations of selected academic library buildings in the Philippines completed between 2001 and 2013 - Gado, Marlon G. 1982- (School of Library and Information Studies, University of the Philippines, Diliman, 2015)
Academic library buildings are important centers for the efficient delivery of library services. In this regard, this study sought to determine the planning and design considerations that led to either satisfaction or dissatisfaction with the academic library buildings completed between 2001 and 2013. In doing so, 10 academic library planning teams were surveyed using a questionnaire adapted from Sannwald (2009) Bennet, (2003) and Stewart, (2009). This study utilized the descriptive method of research. The data gathered from the survey were ranked with "strongly considered" as the highest and "never considered" as the lowest rank.